Mean Airway Pressure as A Predictor of Mortality (Short Term) InMechanically Ventilated ARDS Patients (The Planet, 2024)
Introduction: The prognostic value of mean airway pressure (MAP) in mechanically ventilated patients with acute respiratory distress syndrome (ARDS) remains inadequately explored, despite its potential as a readily available monitoring parameter. This study investigated the relationship between MAP and short-term mortality in ARDS patients. Methods & Materials: In this single-center observational cohort study, we analyzed data from 122 adult patients with ARDS requiring mechanical ventilation. We recorded demographic characteristics, ventilatory parameters, and clinical outcomes. The primary outcome was 28-day mortality. Multivariate logistic regression analysis was performed to assess the independent association between MAP and mortality, while receiver operating characteristic (ROC) curve analysis determined the optimal predictive threshold. Results: The overall 28-day mortality rate was 31.1% (38/122 patients). Non-survivors demonstrated significantly higher MAP values compared to survivors (18.9 ± 3.6 vs. 14.2 ± 3.2 cmH2O, p
Keywords: Acute Respiratory Distress Syndrome; Mean Airway Pressure; Mechanical Ventilation; Mortality; Prognostic Factor